Gattaca [videorecording (DVD)] - Niccol, Andrew; Niccol, Andrew; Hawke, Ethan, 1970-; Thurman, Uma; Arkin, Alan; Law, Jude, 1972-; Dean, Loren, 1969-; Vidal, Gore, 1925-2012; Borgnine, Ernest, 1917-2012 (Columbia TriStar Home Video, 1998)
Story about an all-too-human man who dares to defy a system obsessed with genetic perfection. Vincent is an "In-Valid," who assumes the identity of a member of the genetic elite to pursue his goal of traveling into space with the Gattaca Aerospace Corporation. However, a week before his mission, a murder marks Vincent as a suspect. With a relentless investigator in pursuit and the colleague he has fallen in love with beginning to suspect his deception, Vincent's dreams steadily unravel.